Potential applications of silver and copper nanoparticles for the control of Penicillium digitatum causing green mould disease on orange fruits in Vietnam - Vu Mai Linh, Nguyen; Thi Hong Thao, Phan; Van Hieu, Nguyen; Thi Hong Lien, Nguyen (VNU Journal of Science: Natural Sciences and Technology, 2017)
Penicillium digitatum is a major source of post-harvest decay on orange fruits. In Vietnam, the control of P. digitatum has been done mostly with use of chemicals which advertly affect local environment and human health. Recently, nanomaterials show significant effectiveness in treating pathogenic fungi without harming the environment and human health. Therefore, nanomaterials are regarded as promising agents in plant protection and post-harvest processing. In this study, a fungus labeled as N11 causing green mould disease was isolated from orange fruits of Tuyen Quang province and identified as Penicillium digitatum N11. The fungus was subjected to treatment with silver and copper nanoparticles and nanocomposites to evaluate the effectiveness of those materials in inhibition of fungal growth. Various concentrations of the nanoparticles were tested at different growth stages of the fungus. For silver and copper nanoparticles, the inhibition of fungal growth up to 50% was observed for 21 days at the concentrations of 200 ÷ 400 ppm and 250 ppm, respectively. At 500 ppm, copper nanoparticles completely inhibited the growth of Penicillium digitatum N11. Nano composite Ag-silica (AgS) showed stronger inhibition of fungal growth than Ag-Bentonite (AgB) nanocomposite. In the treatment of fungal spores, inhibition of germination up to 90% for three days was observed at the concentrations of 1000 ppm for Cu, above 200 ppm for Ag  nanoparticles, over 2000 ppm of AgS nanocomposite and 4000 ppm of AgB nanocomposite